PEMBERDAYAAN USAHA MIKRO BERBASIS ZAKAT, INFAK DAN SEDEKAH (ZIS) DI LAZ DAUD BOGOR - Tamami, Rijal; Casmita Pujiharto, Yaya Ruhenda; Sumenkar, Apung (Institut Agama Islam Sahid Bogor, 2025)
Micro enterprises play a crucial role in national economic development but often face challenges, particularly in accessing capital and financing. This study aims to examine the mechanisms of collection, management, and distribution of Zakat, Infak, and Sedekah (ZIS) funds by LAZ Daud Bogor in supporting micro enterprise empowerment, as well as to analyze the internal and external factors influencing the program through SWOT analysis. The research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation at LAZ Daud Bogor and its affiliated micro enterprise community. The results indicate that the ZIS fund management mechanism operates in a structured and transparent manner, focusing on capital provision, training, market access, community network strengthening, product development, and sustainability of micro enterprises. The SWOT analysis identifies strengths such as stable funding sources and solid community networks, weaknesses including limited human resources and monitoring, opportunities from government support and digital technology, and threats such as economic instability and market competition. The strategic position of the program lies in the Strengths-Opportunities (SO) quadrant, enabling the implementation of aggressive and innovative strategies to expand social and economic impact sustainably. This study provides strategic recommendations to enhance the effectiveness of micro enterprise empowerment based on ZIS at LAZ Daud Bogor.